Climate resilient organic farming for groundnut (Arachis hypogaea)-garlic (Allium sativum) crop sequence - Mathukia, R.K.; Sheikh, M.A.; Sagarkaand, B.K.; Panara, D.M. (Annals of Agricultural Research, 2016)
A field experiment was conducted at Junagadh on clayey soil during 2009-10 to 2011-12 at Junagadh (Gujarat) to evaluate the potentiality of organic farming in groundnut-garlic crop sequence in terms of productivity, profitability and soil health. Treatments comprised FYM, poultry manure, vermicompost and crop residues (applied on equivalent N basis) and RDF. Results revealed that application of FYM and vermicompost recorded significantly higher pod yield (1533 and 1413 kg/ ha) and haulm yield (3146 and 3288 kg/ha) of groundnut as compared to RDF. While RDF and FYM recorded significantly higher bulb yield (6134and 5665 kg/ha) of garlic. Maximum net return and B:C ratio were obtained with FYM in groundnut and garlic. Application of FYM and VC to groundnut, while that of RDF and FYM to garlic significantly increased uptake of N, P and K. Application of FYM slightly improved post harvest bulk density, organic carbon, and availability of N, P and K in soil. Â